Community risk of environmental-borne cystic echinococcosis transmission in South America: Results from the multistep cross-sectional and case-control PERITAS study. - Gerardo Acosta-Jamett; Francesca Tamarozzi; Natalia Castro; Saul J Santivanez; Raul Enriquez Laurente; Cristina Mazzi; Cristian A Alvarez-Rojas; Adriano Casulli (PLoS Neglected Tropical Diseases)
Background Cystic echinococcosis (CE) is mainly described as a food/waterborne zoonosis. However, evidence about matrices contamination is scarce. Identifying main transmission routes could optimize health messages aiming to prevent ingestion of parasite eggs. We evaluated Echinococcus granulosus contamination of matrices in two areas of Chile and Peru. Methodology/principal findings In stage 1, areas with high active CE prevalence were identified through cross-sectional ultrasound surveys. Stage 2 was a case-control study encompassing matrices sampling in public places and households with and without CE cases in these areas, followed by (stage 3), matrices processing by sequential sieving and E. granulosus detection by PCR. Bayesian multilevel mixed-effects logistic regression analysis was used to identify factors associated with risk of contamination. In households, soil (19%-42%); dogs' fur (10%-30%); shoes' soles (5%-33%); and dogs' feces (0-50%) were highly contaminated. In public areas, ~ 30% of fecal and soil samples were contaminated. Overall, matrices from public areas were more contaminated than those from households. When examining households, there was no difference in risk of contamination according to presence of CE cases, while CE-free households had lower risk when considering households and public areas. There was no difference in risk of contamination according to matrix. Vegetables were PCR-negative. Conclusions/significance Results suggest the need for a paradigm-shift towards considering CE an environmental-borne infection with a "community risk" to which people are exposed.